2010
DOI: 10.1021/jp102174y
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanoparticles Produced by Femtosecond Laser Ablation in Ethanol: Size Control, Structural Characterization, and Optical Properties

Abstract: Spherical silicon nanoparticles were prepared by laser ablation of a single crystal Si wafer immersed in 95% ethanol with a pulse duration shorter than the time of electron−phonon relaxation (from 35 to 900 fs). The size distribution depends on the pulse duration as well as the width of the size distribution, which increases with the increase of the laser pulse duration. High resolution transmission electron microscopy performed on 20−40 nm particles showed polycrystalline particles made up mainly of silicon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 33 publications
4
81
0
2
Order By: Relevance
“…Si-NCs are identified by the Raman line at 518 cm −1 , Fig. 2(a); its redshift ( = −2.2 ± 0.2 cm −1 ) and broadening respect to the lineshape related to a bulk Si crystal agree with the phonon confinement effect [18]. The dependence of the peak shift on the Si-NC size (d in nm) is given by the following phenomenological law [19]:…”
Section: Resultsmentioning
confidence: 53%
“…Si-NCs are identified by the Raman line at 518 cm −1 , Fig. 2(a); its redshift ( = −2.2 ± 0.2 cm −1 ) and broadening respect to the lineshape related to a bulk Si crystal agree with the phonon confinement effect [18]. The dependence of the peak shift on the Si-NC size (d in nm) is given by the following phenomenological law [19]:…”
Section: Resultsmentioning
confidence: 53%
“…The chemical and physical information that is currently available on the various elemental silicon systems has been obtained primarily through two significantly disparate approaches: (1) The study of ultra-low surface-area materials (~10 −4 m 2 g −1 ), using ultra-high vacuum (UHV) instrumentation and the techniques of “surface science”, that is, infra-red (IR) spectroscopy [24], scanning tunneling microscopy (STM) [25], atomic force microscopy (ATM) [26], transmission electron microscopy (TEM) [4,27], high-resolution electron energy loss spectroscopy (HREELS) [28] or X-ray photoelectron spectroscopy (XPS) [27], etc. , and (2) the study of high-surface-area materials (~10 2 m 2 g −1 ) by solid-state nuclear magnetic resonance (NMR) [13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the thermal conductivity of the ethanol (0.17 W/mK at 25 • C) is much smaller than that of the water (0.60 W/mK at 25 • C), ethanol solution can get easily vaporized to such an enhanced condition and decomposes into CH 4 , C 2 H, 4 CH 3 CHO and CH 3 gases at very high localized temperature and pressure [18]. It is reported earlier that during laser ablation in ethanol free carbon also generated due to decomposition of ethanol [19,20]. It might be possible that these compounds restrict the oxidation of ablated Co by attaching around it hence a layer of carbon around the cobalt protects the oxidation of Co. Chen et al [21] also reported the synthesis of pure Co NPs in ethanol by liquid phase pulse laser ablation.…”
Section: And Coooh Which Subsequently Decomposes Into Co 3 O 4 and Cmentioning
confidence: 95%